PERANCANGAN DAN IMPLEMENTASI SISTEM LAYANAN PELANGGAN BERBASIS WEB PADA PT YA LOGISTIK MENGGUNAKAN FRAMEWORK LARAVEL - Dylan Fachrezy, Ahmad (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The development of information technology in the digital era has encouraged logistics companies to adapt to web-based service systems to improve efficiency and customer satisfaction. PT YA Logistik, as a company engaged in goods delivery services, requires an integrated customer service system to streamline communication and manage service data effectively. This study aims to design and implement a web-based customer service system for PT YA Logistik using the Laravel framework. The software development method applied is Scrum, which enables the system to be developed gradually and adaptively according to changing user needs. The system provides main features such as shipping rate checking, shipment tracking, complaint management, and delivery data administration. System testing using the Black-box testing method shows that all functions operate according to user requirements without any functional errors. The results of this study indicate that the implementation of a web-based customer service system can improve operational efficiency, accelerate information delivery, and provide easier access to services for PT YA Logistik customers in a digital environment.